2015
DOI: 10.2149/tmh.2014-40
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Postpartum Healthcare Services and Exploring the Challenges and Motivations of Maternal Health Service Providers in the Philippines: a Qualitative Study

Abstract: Background: Given the shortage of medical professionals in the Philippines, Barangay Health Workers (BHWs) may play a role in providing postpartum healthcare services. However, as there are no reports regarding BHW activities in postpartum healthcare, we conducted this study to understand postpartum healthcare services and to explore the challenges and motivations of maternal health service providers. Methods: Focus group interview (FGI) of 13 participants was conducted as qualitative research methodology at M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…Participants manifested that other health care institutions such as community health centres and private institutes, were not trustworthy because of their poor equipment, less experienced and less qualified health care professionals, and high costs. This finding suggests that standardized professional training and financial input should be offered to primary medical facilities to improve their service quality and further complement hospital health care services [50][51][52].…”
Section: Discussionmentioning
confidence: 98%
“…Participants manifested that other health care institutions such as community health centres and private institutes, were not trustworthy because of their poor equipment, less experienced and less qualified health care professionals, and high costs. This finding suggests that standardized professional training and financial input should be offered to primary medical facilities to improve their service quality and further complement hospital health care services [50][51][52].…”
Section: Discussionmentioning
confidence: 98%
“…33 We reported that BHWs could efficiently evaluate a woman’s physical and mental condition through their home visiting services. 34 Therefore, BHWs play an important role in assessing healthcare service utilization and postpartum health conditions in women who deliver at home in the Philippines. Health education on danger signs which is provided not only by professionals, but also by BHWs, could enhance knowledge and attitudes in postpartum women, which could ultimately enrich their health in the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“…Participants manifested that other health care institutions such as community health centres and private institutes, were not trustworthy because of their poor equipment, less experienced and less quali ed health care professionals, and high costs. This nding suggests that standardized professional training and nancial input should be offered to primary medical facilities to improve their service quality and further complement hospital health care services [51][52][53].…”
Section: Discussionmentioning
confidence: 99%